Peningkatan Kesadaran tentang Keamanan Informasi pada Masyarakat Aktif di Kabupaten Indramayu - Anita Muliawati; Widya Cholil; Kraugusteeliana Kraugusteeliana; Ati Zaidiah; Tjahjanto Tjahjanto; Prihandoko Prihandoko; Azim Zaliha binti Abd Aziz (Lembaga Pengembangan Kinerja Dosen, 2025)
Lebu Digita (LeDig) is a program to realize a Smart Village or 'Smart Village' which aims to change the use of digital technology both in community services and in village government administration. The implementation of this program has used sufficient resources, both in terms of funds and other resources provided by the Indramayu Regency Government. This program aims to achieve the development strategy that has been planned by the Indramayu Regency Government and surrounding villages with the main goal of providing digital-based services for the Indramayu Regency Community. The use of a digital-based system must also be supported by strengthening user competencies through a digital literacy training program for village communities. This community service program aims to increase public awareness of information security in using digital media in the LeDig Program can increase productivity, expand markets, and create new jobs in Indramayu Regency. This community service activity also resulted in a measurement of the level of public awareness of information security using an instrument developed based on the COBIT 2019 Framework. From the results of this measurement, it can be determined the follow-up to the community service program that will be carried out next for the community using the LeDig program in Indramayu Regency, the implementation of which was carried out by a research team from the Faculty of Computer Science, UPN Veteran Jakarta in collaboration with partners from UNIZA, Malaysia.Lebu, Digital, Indramayu, Security, information.